2005
DOI: 10.1038/sj.pcan.4500841
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged prostate: A landmark national survey of its prevalence and impact on US men and their partners

Abstract: This questionnaire-based survey evaluated the frequency and severity of lower urinary tract symptoms (LUTS) and the prevalence of enlarged prostate (EP) diagnosis and its impact on quality of life and spousal relationships among 41000 American men aged 450 years. A quarter of men suffered moderate to severe LUTS and 55% of those consulting a doctor had EP. EP negatively affected patient quality of life and caused relationship strain with spouses. These findings confirm that LUTS and EP are prevalent in the US … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 11 publications
1
24
0
2
Order By: Relevance
“…This result and conclusion are compatible with other studies [4][5][6][7][8][9][10]. Inviting the partner to attend at the consultation has benefits for the couple.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This result and conclusion are compatible with other studies [4][5][6][7][8][9][10]. Inviting the partner to attend at the consultation has benefits for the couple.…”
Section: Discussionsupporting
confidence: 95%
“…In a population study, both men with an enlarged prostate and with moderate to severe LUTS symptoms and their partners experienced relationship strains such as lack of physical intimacy and lack of communication [5]. Shvartzman et al [6] telephone-interviewed 215 partners of men with prostatic symptoms and found that in 86% the husbands' urinary symptoms had consequences for the partners' daily routines, social relationships, sex life and quality of life.…”
Section: Introductionmentioning
confidence: 98%
“…Histological evidence of BPH is found in 50% of males by the age of 50 and 90% of males by the age of 80 [63]. The development of BPH depends on androgens, and BPH does not occur in men castrated prior to puberty [64].…”
Section: Clinical Role Of 5α-rmentioning
confidence: 99%
“…1 Many of these individuals develop lower urinary tract symptoms (LUTS) associated with prostatic enlargement and bladder outlet obstruction. Men with enlarged prostates often experience progressive worsening of clinical symptoms over time, including decreased maximum urinary flow rate (Q max ).…”
Section: Introductionmentioning
confidence: 99%